Hydrogen Production Through Water Splitting Reaction Using Titanium Dioxide (Tio2) Nanotubes Photocatalyst - ., Mohdhasmizamrazali; Ismail, Nurarifah; Mat Amin, Khairulanuar (International Journal of Engineering and Technology, 2018)
Nowadays, the most ideal process for hydrogen production is to use water as a hydrogen source through water splitting reaction with the present of the titanium dioxide photocatalysts. Titanium dioxide nanotubes (TiO2-NTâ€™s) was synthesized using facile hydrothermal method. TEM micrograph shows that the synthesized TiO2-NTâ€™s had tubular structure with â€œhair-likeâ€ nanoscopic filaments with large specific surface area, which is needed to be a high performance photocatalyst. The saiz of nanotube are 4 nm and 10 nm for inner and outer diameters, respectively. Meanwhile, their surface area was found to be 226.52 m2/g. XRD pattern revealed that the phase structure of synthesized TiO2-NTâ€™s was anatase TiO2. Synthesized TiO2-NTâ€™s was tested for hydrogen gas production managed to produce 80 Âµmol after 5 hours reaction.Â Â